Identity and cultural allegory amidst the Chinese new era: Analyzing narrative strategies of the Chinese science fiction film - Zhaokai Hu; Roslina Ismail; Changsong Wang (Cogent Arts & Humanities)
This paper presents a comprehensive analysis of two Chinese science fiction films, The Wandering Earth and Crazy Alien, shedding light on their profound connection to identity and cultural allegory within the context of the Chinese New Era. We employ the Greimas’s actantial model and semantic square to examine the narrative strategies, visual symbols, and cultural representations in these films. The Wandering Earth unfolds a grand narrative anchored in the principles of hard science fiction, the film leverages science and technology as narrative drivers. In contrast, Crazy Alien adopts a more whimsical approach by infusing humor and light science fiction elements into its narrative. From a postmodern standpoint, both films boldly engage with and subvert traditional narratives and cultural depiction shifting the spotlight from an individualistic hero to collective action, employs humor, parody, and absurdity to dismantle established Western science fiction tropes, resisting categorization and fixed binary oppositions while promoting shared aspirations of a community, thus challenging the modernist notion of the solitary hero’s agency. However, it is imperative to critically examine the potential limitations of these films, including their alignment with nationalist narratives and their appropriation of Western cultural elements. This study provides valuable insights into the evolving realm of Chinese science fiction film, where the fusion of traditional Chinese elements with global influences fuels thought-provoking discussions within the global cinematic discourse.